PENINGKATAN KAPASITAS KADER POSYANDU MELALUI INOVASI OLAHAN PMT BERBAHAN DASAR IKAN DAN SAYURAN - Rahayu, Widya; Sari, Dahlia Wulan; Siregar, Achis Martua; Septiana, Septiana; Andriana, Ria; Ningsih, Sulistia; Harfinda, Elliska Murni; Pangestu, Gigih Budhiawan; Saloko, Yogo Tri; Qurniasih, Ilmawati; Ceri, Bunia; Meiratania, Marisa; Rustianti, Ida (Bina Bahari, 2025)
upplementary Feeding (PMT) is a vital service at Integrated Healthcare Centers (Posyandu) that requires balanced nutritional content and varied preparations. Therefore, training on innovative PMT preparation for healthcare cadres is essential. This community service activity aimed to develop innovative PMT based on fish and vegetable preparations, featuring balanced nutrition and an appealing taste. This activity involved eight cadres from the Sedap Malam Integrated Healthcare Center and was conducted in three stages: preparation, implementation, and evaluation. The preparation stage identified partner needs, while the implementation included material delivery and hands-on practice. At the end of the activity, an organoleptic test was conducted on the resulting products. The organoleptic test results showed a high acceptance rate for the fish-based PMT innovation, with an average preference score of 84.4% for taste, color, and texture. This product can serve as a solution for fulfilling toddler nutrition. Similar activities should be developed involving various parties, such as the government, universities, and the private sector.